Should we Consider Lipoprotein (a) in Cardiovascular Disease Risk Assessment in Patients with Familial Hypercholesterolaemia? - Anagnostis, Panagiotis; Siolos, Pavlos; Krikidis, Dimitrios; Goulis, Dimitrios G.; Stevenson, John C. (Current Pharmaceutical Design, 2018)
Background: Familial hypercholesterolaemia (FH) is a genetically determined lipid disorder, affecting 1 per 200-500 individuals in the general population. It is significantly and independently associated with an increased risk of Cardiovascular Disease (CVD), although it remains still an underrecognized and undertreated disease. Lipoprotein (a) [Lp(a)] is a low-density-lipoprotein (LDL)-like molecule, containing an additional protein, apolipoprotein (a). Objective: This review aims to present and discuss available data on the role of Lp(a) in patients with FH, in terms of its potential augmentation of CVD risk. Methods: A comprehensive search of the literature was performed to identify studies evaluating the CV effects of Lp(a) in patients with FH. Results: Lp(a) has been recognised as an independent risk factor for CVD, mainly coronary artery disease (CAD). Most, but not all, studies show increased Lp(a) concentrations in adults and children with FH. There is also evidence of an independent association between Lp(a) and CVD (mainly CAD) risk in these patients. Conclusion: Some therapeutic modalities, such as niacin, oestrogens, tibolone and proprotein convertase subtilisin/ kexin type 9 (PCSK9) inhibitors may effectively reduce Lp(a) concentrations by 25-30%, although their clinical benefit of this effect remains to be established.
Keywords: Familial hypercholesterolaemia